2018
DOI: 10.1016/j.jhep.2018.04.023
|View full text |Cite
|
Sign up to set email alerts
|

A combined model based on spleen stiffness measurement and Baveno VI criteria to rule out high-risk varices in advanced chronic liver disease

Abstract: Background & Aims: Recently, Baveno VI guidelines suggested that esophagogastroduodenoscopy (EGD) can be avoided in patients with cACLD who have a liver stiffness measurement (LSM) < 20 kPa and platelet count >150,000/mm 3. We aimed to: assess the performance of spleen stiffness measurement (SSM) in ruling out patients with high-risk varices (HRV); validate Baveno VI criteria in a large population and assess how the sequential use of Baveno VI criteria and SSM could safely avoid the need for endoscopy. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
138
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 153 publications
(154 citation statements)
references
References 41 publications
13
138
3
Order By: Relevance
“…In this issue of Digestive Diseases and Sciences, Karagiannakis and colleagues [4] report for the first time how SSM measured using ultrasonic two-dimensional shear wave elastography (2D-SWE) improves the ability of the Baveno VI criteria to risk-stratify cirrhotic patients for the presence of VNT, safely reducing the number of unnecessary EGDs. The authors not only confirmed our findings [3] but also showed that the measurement of SSM alone can reduce, in a cohort of cirrhotic patients, the number of unnecessary EGDs performed. Identifying new specific SSM cutoffs for 2D-SWE, they were able to spare more than 40% of EGDs in a cirrhotic cohort of 71 patients, achieving a missed VNT rate < 5%, an arbitrary threshold included in the Baveno recommendations [1].…”
supporting
confidence: 85%
See 1 more Smart Citation
“…In this issue of Digestive Diseases and Sciences, Karagiannakis and colleagues [4] report for the first time how SSM measured using ultrasonic two-dimensional shear wave elastography (2D-SWE) improves the ability of the Baveno VI criteria to risk-stratify cirrhotic patients for the presence of VNT, safely reducing the number of unnecessary EGDs. The authors not only confirmed our findings [3] but also showed that the measurement of SSM alone can reduce, in a cohort of cirrhotic patients, the number of unnecessary EGDs performed. Identifying new specific SSM cutoffs for 2D-SWE, they were able to spare more than 40% of EGDs in a cirrhotic cohort of 71 patients, achieving a missed VNT rate < 5%, an arbitrary threshold included in the Baveno recommendations [1].…”
supporting
confidence: 85%
“…For the first time last year, the authors combined the measurement of spleen stiffness (SSM), as assessed by TE, with the Baveno VI criteria in a diagnostic algorithm aiming to improve its performance. The algorithm was tested in a cohort of > 500 patients with advanced chronic liver disease (ACLD), demonstrating that is possible to correctly identify VNT while decreasing the number of EGDs needed to identify VNT [3].…”
mentioning
confidence: 99%
“…Thus, the papers aiming to validate these criteria have used three different methods to calculate missed VNT. In all of them, the numerator was the number of missed VNT, but the denominator was either: the number of spared endoscopies, as done by Bae et al in a recent issue of this journal; the number of VNT, as we did recently also in this journal and elsewhere; or the whole patient population, as done by Augustin et al Therefore, our aim with the present work was to perform a literature review and analyse the calculation methods to clarify their diagnostic meaning.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the spleen stiffness (SS) measurement is potentially an alternative test to assess the presence and severity of PH in a non‐invasive way. TE is currently the most commonly used technique to assess SS, but measuring SS by ARFI methods and pSWE too has been evaluated for predicting the presence and degree of PH, and has given promising data, whereas the role of these techniques in detecting any presence of OVs is still sub‐optimal …”
Section: Introductionmentioning
confidence: 99%
“…8,9 Thus, the spleen stiffness (SS) measurement is potentially an alternative test to assess the presence and severity of PH [10][11][12][13][14][15][16] in a non-invasive way. TE is currently the most commonly used technique to assess SS, 14,17,18 but measuring SS by ARFI methods and pSWE too has been evaluated for predicting the presence and degree of PH, [18][19][20] and has given promising data, whereas the role of these techniques in detecting any presence of OVs is still sub-optimal. [21][22][23] We performed a prospective single-centre cohort study in order to investigate the feasibility and reproducibility of the SS measurement by using pSWE in a cohort of consecutive patients with CLDs of different aetiology who underwent liver biopsy.…”
Section: Introductionmentioning
confidence: 99%